2018
DOI: 10.2500/aap.2018.39.4123
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary angioedema from the patient's perspective: A follow-up patient survey

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 25 publications
0
17
0
4
Order By: Relevance
“…das an den Bradykinin-2-Rezeptor (B2R) bindet [ 5 ] . Die Häufi gkeit von HAE-Attacken kann von wenigen bis zu mehr als 100 pro Jahr variieren [ 6,7 ] . Die in der Literatur geschätzte Prävalenz der Krankheit reicht von 1 : 10.000 bis 1 : 150.000 [8][9][10] .…”
Section: Resultsunclassified
“…das an den Bradykinin-2-Rezeptor (B2R) bindet [ 5 ] . Die Häufi gkeit von HAE-Attacken kann von wenigen bis zu mehr als 100 pro Jahr variieren [ 6,7 ] . Die in der Literatur geschätzte Prävalenz der Krankheit reicht von 1 : 10.000 bis 1 : 150.000 [8][9][10] .…”
Section: Resultsunclassified
“…10 Another topic frequently addressed in previous issues of the Proceedings as well as in the current issue is hereditary angioedema (HAE), a condition that manifests as episodic swelling, most often resulting from deficiency of C1-inhibitor and associated with dysregulation of the contact activation system. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Currently, there is limited real-world evidence on characteristics of patients with HAE and health-care resource utilization. To help fill this void, Tachdjian et al 26 performed a retrospective cohort study by using data from PharMetrics Plus, an administrative claims data base that includes a large U.S. cohort of adult and pediatric patients who received treatments indicated or used for HAE.…”
mentioning
confidence: 99%
“…In moving on to another rare cutaneous disease, hereditary angioedema (HAE) is an autosomal dominant, genetic disorder associated with C1-inhibitor deficiency, which has been a recurrent topic in the Proceedings due to the recent development of a multitude of novel treatment options. [12][13][14][15][16][17][18][19][20][21][22][23][24] In this issue, Arce-Ayala et al 25 reported on the clinical profile and quality of life displayed by Puerto Rican patients with HAE. Compared with U.S. population norms for quality-oflife measures, in Puerto Rico, patients with HAE manifested significantly lower scores, both in the physical and mental components.…”
mentioning
confidence: 99%